Surgery After Conversion Therapy With PD-1 Inhibitors Plus Tyrosine Kinase Inhibitors Are Effective and Safe for Advanced Hepatocellular Carcinoma: A Pilot Study of Ten Patients - Zhang, Wenwen; Hu, Bingyang; Han, Jun; Wang, Zhanbo; Ma, Guangyu; Ye, Huiyi; Yuan, Jing; Cao, Junning; Zhang, Ze; Shi, Jihang; Chen, Mingyi; Wang, Xun; et al. (Frontiers in Oncology, 2021)
Background and Aims Immunotherapy with PD-1 inhibitors combined with tyrosine kinase inhibitors (TKIs) has been proven to be effective against advanced hepatocellular carcinoma (HCC). The aim of this study was to identify the feasibility and safety of subsequent salvage surgery after this combination therapy. Methods and Patients A retrospective analysis was performed on patients with primary HCC with major vascular invasion between 2018 and 2019. All cases were treated with a combination of a PD-1 inhibitor and TKI agents and subsequent surgery. Results A total of 10 HCC cases with major vascular invasion met the successful conversion criteria after the combination therapy, and eight patients underwent subsequent salvage surgery after both radiology and 3D quantitative oncological assessment. Partial response (PR) was recorded in 7 of 10 patients and complete response (CR) in 3 of 10 patients before salvage surgery. Salvage surgery included right hepatectomy, left hepatectomy, and anatomic segmental hepatectomy. The mean intraoperative blood loss was 1,650 ml (50–3,000 ml). No complications beyond Clavien–Dindo level III or postoperative mortality were observed. The viable tumor cell rate of the PR cases (modified response evaluation criteria in solid tumors, mRECIST) varied from 1.5% to 100%, and only one patient had pathology-proven pathological complete response (pCR). The postoperative median follow-up time was 19.7 months (9.1–24.9 months). The 12-month recurrence-free survival rate of all cases who underwent salvage surgery was 75%. Conclusion Salvage surgery was effective and safe after conversion therapy with PD-1 inhibitors plus TKIs and may increase the long-term oncological benefit for patients with unresectable HCC.